Analyzing the load distribution of four-row tapered roller bearing with Boundary Element Method. (July 2015) - Yang, Xia; Huang, Qingxue; Yan, Chuang
Abstract: A Boundary Element Method (BEM) is used to study the roller bearing contact problem due to its high non-linearity. The plate units are used to simulate the rollers, the bearing boundary elements are used to realize the discontinuous nature of the traction on the contact area, and the Hertz contact theory is used to revise contact widths between rollers and the inner and outer races. According to assembly and fit characteristics of rolling mill tapered roller bearings, in which both clearance fits are adopted to the inner race with the mill roll and the outer race with the shaft block, the four-objects elastic frictional contact program of bearing BEM is compiled, with which a rolling mill four-row tapered roller bearing is simulated. The shaft block direct measure method is used to measure the load distribution of the four-row tapered roller bearing. The experimental data and the result of simulation are compared, and the load distribution laws of simulation identify with the test result, which proves the validity and effectiveness of using elastic frictional contact BEM to analyze the load distribution of bearing.